ABCG9, ABCG11 and ABCG14 ABC transporters are required for vascular development in Arabidopsis. (December 2013) - Le, Rozenn; Sorin, Clément; Chakraborti, Dipankar; Moritz, Thomas; Schaller, Hubert; Tellier, Frédérique; Robert, Stéphanie; Morin, Halima; Bako, Laszlo; Bellini, Catherine
Summary In order to obtain insights into the regulatory pathways controlling phloem development, we characterized three genes encoding membrane proteins from the G sub‐family of ABC transporters (ABCG9, ABCG11 and ABCG14), whose expression in the phloem has been confirmed. Mutations in the genes encoding these dimerizing 'half transporters' are semi‐dominant and result in vascular patterning defects in cotyledons and the floral stem. Co‐immunoprecipitation and bimolecular fluorescence complementation experiments demonstrated that these proteins dimerize, either by flexible pairing (ABCG11 and ABCG9) or by forming strict heterodimers (ABCG14). In addition, metabolome analyses and measurement of sterol ester contents in the mutants suggested that ABCG9, ABCG11 and ABCG14 are involved in lipid/sterol homeostasis regulation. Our results show that these three ABCG genes are required for proper vascular development in Arabidopsis thaliana.